The Relationship between Preeclampsia and Premature Incidence Rates - Ariana Lutfi Komariah; Sunanto; Iis Hanifah (KHD Production, 2023)
Preeclampsia and eclampsia are causes of death in mothers whose incidence rates progressively increase yearly. Premature birth is one of the complications that can occur in pregnant women who suffer from preeclampsia, where premature birth is one of the causes of morbidity and mortality in infants. This study aims to analyze the relationship between preeclampsia and the incidence of prematurity. This research is an analytical observationalstudy with a cross-sectional. The sample in this study was 35 samples of mothers who had preeclampsia and then analyzed using the Chi-square. The proportion of preeclampsia cases resulting in preterm labor was 13 (2.6%), with p=0.000. Conclusion. There is a relationship between preeclampsia and the number of premature events at the Paiton Health Center in 2021. It is hoped that the Paiton Health Center in Probolinggo Regency will evaluate the completeness of medical record filing and conduct early education for patients who are at risk or who do not have a risk for preeclampsia or premature events so that education can be carried out. early prevention and follow-up of patients who have been diagnosed with preeclampsia or in patients who are predicted to have preterm labor inorder to receive early treatment to increase survival rates and quality of life of patients and fetuses.